2017
DOI: 10.9734/isrr/2017/36373
|View full text |Cite
|
Sign up to set email alerts
|

Use and Effectiveness of HIV Indicator Conditions in Guiding HIV Testing: A Review of the Evidence

Abstract: Aims: To identify the most commonly reported HIV indicator conditions (HIV ICs) found in or associated with HIV infection and to review interventions incorporating HIV ICs to aid or guide offering of an HIV test and discuss their effectiveness in increasing HIV testing rates and diagnosing new cases of HIV-infection. Methodology: The following electronic databases were searched; OVID Medline, Google, Web of Science and PubMed. We included studies conducted in high income countries within the adult population (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…The system was found to be useable and acceptable by hospital doctors, GPs and nurses and there was a 6% increase in testing rates over the 3-month study period [54]. A recent literature review has provided evidence that HIV ICs have the potential to be used more effectively as triggers for earlier HIV testing [55].…”
Section: Discussionmentioning
confidence: 99%
“…The system was found to be useable and acceptable by hospital doctors, GPs and nurses and there was a 6% increase in testing rates over the 3-month study period [54]. A recent literature review has provided evidence that HIV ICs have the potential to be used more effectively as triggers for earlier HIV testing [55].…”
Section: Discussionmentioning
confidence: 99%
“…An electronic prompt almost doubled the rates of universal HIV screening by primary care providers in a Midwest practice in the USA and reduced racial disparities 29. Federman et al added a reminder to the medical records within the Veterans Affairs healthcare system in the USA based on the risk factors for HIV, leading to an increase in testing of 369% 12. Schrantz et al developed a web-based patient tracking software to flag selected patients for testing and found an association between the use of the system and a 262% increase in testing frequency (from 29.6 to 80.5 tests per month) 12.…”
Section: Discussionmentioning
confidence: 99%
“…Federman et al added a reminder to the medical records within the Veterans Affairs healthcare system in the USA based on the risk factors for HIV, leading to an increase in testing of 369% 12. Schrantz et al developed a web-based patient tracking software to flag selected patients for testing and found an association between the use of the system and a 262% increase in testing frequency (from 29.6 to 80.5 tests per month) 12. Goetz et al used reminders triggered by STI and behavioural risk factors and found an increase in the frequency of testing and the number of new diagnoses made 12…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that more effective use of HIV ICs has the potential to trigger earlier HIV testing [37]. In support of this finding, a retrospective case-notes review in NHS City and Hackney Primary Care Trust of patients known to be HIV positive found that despite 51 out of 89 (57.3%) patients presenting to their GP with at least one HIV IC in the 2 years prior to diagnosis, only 17 (33.3%) were subsequently diagnosed with HIV by their GP [11].…”
Section: Discussionmentioning
confidence: 99%